Change in trap characteristics during fatigue of Au/BiFeO3/SrRuO3. (May 2020) - Jin, Lei; Zhu, Hui; Chu, Daping; Yang, Ying; Wang, Chen; Xie, Na; Huang, Zeng; Liu, Jiahui
Abstract: We studied the change of trap characteristics during fatigue cycling process in Au/BiFeO3 /SrRuO3 . The resistive switching effect of the structure was caused by the trapping/detrapping of charge carriers. The correlated trap states were analyzed by using the current transient method, which can extract a more complete trap information at low temperature compared with that at the room temperature, because of the slowing down of the thermally activated detrapping behavior as the temperature decrease. The time constant of the traps during fatigue increased first and then decreased, while the trap levels remained unchanged. A new time constant and trap level can be generated by fatigue at low temperature. We attributed such variation in trap characteristics to the change of polarization ordering and trap densities caused by the release of polarization domains in the wake-up stage and by generation of oxygen vacancies during fatigue.